Frightened, disturbed, dangerous? : why working with patients in psychiatric care can be really difficult, and what to do about it /: why working with patients in psychiatric care can be really difficult, and what to do about it. (2017) - Elvén, Bo Hejlskov; Abild, Sophie
No abstract available